Exploration of bacterial communities for low-density polyethylene (LDPE) degradation in the mangrove area of Pamekasan, East Java, Indonesia - JUALITA FARADHA ACHNASYA; ARTINI PANGASTUTI; SITI LUSI ARUM SARI (Society for Indonesian Biodiversity, 2026)
Abstract. Achnasya JF, Pangastuti A, Sari SLA. 2026. Exploration of bacterial communities for low-density polyethylene (LDPE) degradation in the mangrove area of Pamekasan, East Java, Indonesia. Biodiversitas 27 (3): d270325. https://doi.org/10.13057/biodiv/d270325. Low-density polyethylene (LDPE) is one of the most widely used synthetic plastics and a major contributor to persistent pollution in coastal ecosystems, including mangrove environments. Mangroves act as natural sinks for plastic debris, yet the diversity and functional potential of plastisphere-associated bacteria in these systems remain insufficiently understood. This study investigated bacterial community dynamics during LDPE-driven enrichment and identified indigenous LDPE-degrading bacteria from mangrove sediments in Pamekasan, East Java, Indonesia. Sediment samples from three mangrove sites were subjected to three sequential enrichment cultures using carbon-free marine medium with LDPE beads as the sole carbon source. Microbial community shifts were analyzed through metagenomic sequencing, while LDPE degradation capacity was evaluated using gravimetric weight loss, FTIR spectroscopy, and SEM-EDX analyses. Enrichment resulted in pronounced restructuring of bacterial communities, characterized by reduced richness but increased functional specialization across culture stages. Dominant taxa included Qipengyuania, Flavobacterium, Acinetobacter, Pseudoxanthomonas, and Pseudomonas, with a stable core of ASVs persisting throughout enrichment. From the tertiary culture, three culturable isolates demonstrated LDPE-degrading potential: Microbacterium aurantiacum K2, Microbacterium sp. K3, and Bacillus sp. K5. Among these, Bacillus sp. K5 exhibited the highest degradation efficiency, achieving 21.35% LDPE weight loss, followed by Microbacterium sp. K3 (20.27%) and M. aurantiacum K2 (17.10%). FTIR and SEM analyses confirmed oxidative surface modification and structural damage of LDPE films. These findings demonstrate that mangrove plastisphere communities harbor specialized bacteria capable of initiating LDPE degradation and highlight the ecological role of enrichment-driven microbial selection. The study provides a foundation for developing nature-based and environmentally compatible strategies for mitigating plastic pollution in coastal ecosystems.